Sistem Pendukung Keputusan Metode Sugeno dalam Menentukan Tingkat Kepribadian Siswa Berdasarkan Pendidikan - Hakim, Wildan; Turmudi, Turmudi (CAUCHY, 2015)
Sugeno method is one method of fuzzy inference system on fuzzy logic for decision making. In-Zero Order Sugeno method in fuzzy logic consists of four stages: 1. fuzzification. 2. The application functionality implications, the implication function used is function MIN (minimum). 3. The composition rule using the function MAX (maximum). 4. Defuzzification weight average. Based on case 1, each student with non-formal education and informal education by 12 by 19 has a value of 20.7 and a variable linguistic personality is MEDIUM. Suggestions for further research can use other parameters in determining the level of personality of students with fuzzy logic